Comparative genomics reveals new insights into the evolution of the IncA and IncC family of plasmids - Zhang, Fengwei; Ye, Xianwei; Yin, Zhiqiu; Hu, Mingda; Wang, Boqian; Liu, Wenting; Li, Beiping; Ren, Hongguang; Jin, Yuan; Yue, Junjie (Frontiers in Microbiology, 2022)
Incompatibility groups IncA and IncC plasmids are of great concern due to their ability to disseminate antibiotic resistance in bacteria via conjugative transfer. A deep understanding of their genomic structures and evolutionary characteristics is of great significance for improving our knowledge about its multidrug-resistance evolution and dissemination. However, current knowledge of their backbone structure, features of core functional modules and the characteristics of variable regions is based on a few plasmids, which highlights the need for a comprehensive systematic study. The present study thoroughly compared and analysed 678 IncA and IncC plasmid genomes. We found that their core functional genes were occasionally deficient and sometimes existed as multiple functional copies/multiple families, which resulted in much diversity. The phylogeny of 13 core functional genes corresponded well to the plasmid subtypes. The conjugative transfer system gained diverse complexity and exhibited many previously unnoticed types with multiple combinations. The insertion of mobile genetic elements (MGEs) in plasmids varied between types and was present in 4 hotspots in different types of plasmids with certain types of transposons, integrons and insertion sequences. The impact of gene duplication, deletion, the insertion of MGEs, genome rearrangement and recombination resulted in the complex dynamic variable backbone of IncA and IncC plasmids. And IncA and IncC plasmids were more complex than their closest relative SXT/R391 integrative conjugative elements (ICEs), which included nearly all of the diversity of SXT/R391 in key systems. Our work demonstrated a global and systematic view of the IncA and IncC plasmids and provides many new insights into their genome evolution.